White matter abnormalities in long-term heroin users: a preliminary neuroimaging meta-analysis. (March 2015) - Wollman, Scott C.; Alhassoon, Omar M.; Stern, Mark J.; Hall, Matthew G.; Rompogren, Joscelyn; Kimmel, Christine L.; Perez-Figueroa, Adlyn M.
Abstract Background: Diffusion tensor imaging has been used to explore white matter changes in heroin-dependent patients; however, results have been inconsistent. Objectives: The current study meta-analytically examines the neuroimaging findings of all studies published before 2014 using the novel technique of Effect Size Signed Differential Mapping (ES-SDM). Methods: Two independent investigators searched three databases for whole-brain voxel-based fractional anisotropy morphometric studies involving heroin use without comorbid polysubstance abuse. Of 59 initial primary studies, four met stringent inclusion criteria. Results: Results from this preliminary analysis indicate that heroin abusers may have significant reductions in fractional anisotropy in the bilateral frontal sub-gyral regions extending from the limbic structures to the prefrontal association cortices, implicating damage to the cingulum and superior longitudinal fasciculus. Exploratory moderator analyses indicate that the potential damage in the left cingulate gyrus may increase with longer use and decrease after long-term abstinence. Conclusion: These preliminary findings suggest that heroin abuse is significantly associated with damage to white matter integrity. These results are considered preliminary and analyses should be revisited with more primary studies focusing on either long- or short-term abuse as well as abstinence.